2023
DOI: 10.1055/a-2053-7904
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Maternal Diabetes during Pregnancy Is Associated with Aggravated Short-Term Neonatal and Neurological Outcomes following Perinatal Hypoxic–Ischemic Encephalopathy

Abstract: Background: Infants of diabetic mothers are at higher risk of perinatal morbidities and glycemic instability, but the impact of maternal diabetes on neonatal and neurological short-term outcomes of neonates with hypoxic-ischemic encephalopathy (HIE) remains poorly described. Objectives: To determine the impact of maternal diabetes on neonatal and neurological short-term outcomes following neonatal HIE. Methods: A retrospective single-center study including 102 term neonates with HIE who received therapeutic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…A study revealed a difference of 7 days in infants born to mothers with and without diabetes if they were treated with neonatal hypothermia . 5 This difference could be due to maternal diabetes but more importantly re ect the effect of HIE on the infants. The current study excluded infants with encephalopathy to avoid this confounding in uence of encephalopathy on oral feeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study revealed a difference of 7 days in infants born to mothers with and without diabetes if they were treated with neonatal hypothermia . 5 This difference could be due to maternal diabetes but more importantly re ect the effect of HIE on the infants. The current study excluded infants with encephalopathy to avoid this confounding in uence of encephalopathy on oral feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have also compared the incidence and mode of feeding with the future incidence of diabetes in the infants of mothers with diabetes. Although a retrospective study of term neonates with hypoxic ischemic encephalopathy (HIE) treated with therapeutic hypothermia (TH) identi ed a 7-day difference in the time to oral feedings in the infants of mothers with and without diabetes, 5 no study to date has evaluated the difference between time to oral feedings in infants born to mothers with and without diabetes who did not have HIE.…”
Section: Introductionmentioning
confidence: 99%